2013
DOI: 10.1097/qai.0b013e31829a2ef8
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of HSP40/DNAJ in the Regulation of HIV-1 Replication

Abstract: This is the first report providing evidence that HSP70-HSP40 complex confers an innate resistance specific to HIV-1. For their interferon-inducible nature, HSP40 family members should account for the anti-HIV-1 function of interferon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Chaperone HSPA4 (HSP70) inhibits viral gene expression and replication [ 108 ]. Its co-chaperone DNAJ (HSP40) has been associated with both activation and inhibition of viruses, including HIV [ 109 ]. Ubiquitination by TRIM25 increases the ability of RIG-1 to initiate antiviral signaling by facilitating its interaction with MAVS.…”
Section: Discussionmentioning
confidence: 99%
“…Chaperone HSPA4 (HSP70) inhibits viral gene expression and replication [ 108 ]. Its co-chaperone DNAJ (HSP40) has been associated with both activation and inhibition of viruses, including HIV [ 109 ]. Ubiquitination by TRIM25 increases the ability of RIG-1 to initiate antiviral signaling by facilitating its interaction with MAVS.…”
Section: Discussionmentioning
confidence: 99%
“…MRJ-S mainly localizes to the cytoplasm while MRJ-L distributes both to the cytosol and the nucleus ( Cheetham et al, 1992 ). It has been suggested that the conserved DNAJ domain was responsible for HSP40's ability to inhibit HIV-1 production ( Urano et al, 2013 ). Our results show that a significant correlation is found between levels of macrophage MRJ-L expression and levels of HIV-1 infection among high-risk subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of DNAJB12 as a potentially important gene is reminiscent of the observation that the HSP40/DNAJ family proteins play a role in infection of various viruses. Urano and colleagues identified DNAJ/HSP40B6 as a potential regulator of HIV-1 replication [ 40 ]. It is an interesting finding considering the attention that another chaperone, namely HSP90, has recently attracted: HSP90 could promote infectiousness of HIV by controlling HIV reactivation from latency [ 41 ] and several inhibitors of HSP90 are currently in clinical development [ 42 ].…”
Section: Resultsmentioning
confidence: 99%